2015
DOI: 10.1371/journal.pone.0144342
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Estimation of Pelvic Floor Muscle Activity from Transperineal Ultrasound Imaging in Men

Abstract: PurposeTo investigate the relationship between displacement of pelvic floor landmarks observed with transperineal ultrasound imaging and electromyography of the muscles hypothesised to cause the displacements.Materials and MethodsThree healthy men participated in this study, which included ultrasound imaging of the mid-urethra, urethra-vesical junction, ano-rectal junction and bulb of the penis. Fine-wire electromyography electrodes were inserted into the puborectalis and bulbocavernosus muscles and a transure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 25 publications
2
64
0
Order By: Relevance
“…Third, any potential caudal displacement of MU and BP with elevated IAP may be “canceled” by contraction of the muscles to resist lengthening. This would align with previous research that has shown that SUS and BC shorten with an increase in IAP 5 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Third, any potential caudal displacement of MU and BP with elevated IAP may be “canceled” by contraction of the muscles to resist lengthening. This would align with previous research that has shown that SUS and BC shorten with an increase in IAP 5 …”
Section: Discussionsupporting
confidence: 92%
“…Transperineal ultrasound imaging (TPUS) has recently been adapted from work in females 1–3 to assess pelvic floor muscle (PFM) function in males. Use of TPUS in the assessment of urinary incontinence 4,5 and pelvic pain 6 has rapidly been adopted into clinical practice 7 . Previous investigations of male PFM function using TPUS have been performed in supported, reclined long sitting, 4–6,8,9–13 because of the operational ease of ultrasound (US) assessment and retention of the effect of gravity on PFM in this position, but by contrast, TPUS has not been performed in standing before, possibly due to the greater technical difficulty in performing the measures in this position 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐invasive transperineal ultrasound imaging provides an alternative method to study pelvic floor muscle function and recent investigations using this method have provided new insights . Using this technique muscle activation is quantified by displacement of landmarks in the ultrasound images, and this has been validated against measurement of muscle activation using invasive EMG recordings of SUS, PR, and BC . These studies have confirmed a relation between motion observed on ultrasound and activation of individual pelvic floor muscles in healthy men, thus enabling non‐invasive investigation of the continence mechanism in men with PPI.…”
Section: Introductionmentioning
confidence: 82%
“…Transperineal US is increasingly used by physiotherapists and nurses for assessment and biofeedback of pelvic floor muscle activation . These data provide new insight into features of pelvic floor muscle activation that are likely to be relevant for PPI.…”
Section: Discussionmentioning
confidence: 99%